Inhibition of phosphorus removal performance in activated sludge by Fe(III) exposure: transitions in dominant metabolic pathways - Hong, Yiyihui; Cheng, Hong; Huangfu, Xiaoliu; Li, Lin; He, Qiang (Frontiers in Microbiology, 2024)
Simultaneous chemical phosphorus removal process using iron salts (Fe(III)) has been widely utilized in wastewater treatment to meet increasingly stringent discharge standards. However, the inhibitory effect of Fe(III) on the biological phosphorus removal system remains a topic of debate, with its precise mechanism yet to be fully understood. Batch and long-term exposure experiments were conducted in six sequencing batch reactors (SBRs) operating for 155 days. Synthetic wastewater containing various Fe/P ratios (i.e., Fe/P = 1, 1.2, 1.5, 1.8, and 2) was slowly poured into the SBRs during the experimental period to assess the effects of acute and chronic Fe(III) exposure on polyphosphate-accumulating organism (PAO) growth and phosphorus metabolism. Experimental results revealed that prolonged Fe(III) exposure induced a 2 transition in the dominant phosphorus removal mechanism within activated sludge, resulting in a diminished availability of phosphorus for bio-metabolism. In Fe(III)treated groups, intracellular phosphorus storage ranged from 3.11 to 7.67 mg/g VSS, representing only 26.01% to 64.13% of the control. Although the abundance of widely reported PAOs (Candidatus Accumulibacter) was 30.15% in the experimental group, phosphorus release and uptake were strongly inhibited by high dosage of Fe(III).Furthermore, the abundance of functional genes associated with key enzymes in the glycogen metabolism pathway increased while those related to the polyphosphate metabolism pathway decreased under chronic Fe(III) stress. These findings collectively suggest that the energy generated from polyhydroxyalkanoates oxidation in PAOs primarily facilitated glycogen metabolism rather than promoting phosphorus uptake. Consequently, the dominant metabolic pathway of communities shifted from polyphosphate-accumulating metabolism to glycogen-accumulating metabolism as the major contributor to the decreased biological phosphorus removal performance.